Atonement - McEwan, Ian.; Vintage (London : Vintage Books, 2007)
Imaginative thirteen-year-old Briony Tallis, misinterpreting a scene between her older sister Cecilia and Robbie Turner, the housekeeper's son, later accuses Robbie of a crime she has no proof he committed and spends years trying to atone for her actions.
Adult
Keywords: Country life -- England -- Fiction; Dunkirk, Battle of, Dunkerque, France, 1940 -- Fiction; Ex-convicts -- England -- Fiction; Guilt -- Fiction; Sisters -- Fiction; Teenage girls -- England -- Fiction; World War, 1939-1945 -- England -- Fiction; Country life -- Fiction; Domestic fiction; Ex-convicts -- Fiction; Girls -- England -- Fiction; Historical fiction; Psychological fiction; Teenagers -- England -- Fiction; England -- Fiction